Educating teacher ethics in tawhidic paradigm: the Tanzanian experiences - Ibnu Sheikh Gunda, Mnyero Janja; Alwi, Nor Hayati; Abd Rahman, Fadzilah; Krauss, Steven Eric; Hamzah, Azimi (Faculty of Educational Studies, Universiti Putra Malaysia, 2015)
Educating teacher ethics is essential from different traditions, as it for the Islamic paradigm. This phenomenological study seeks to explore how Muslim educators educate teacher ethics from Tawhidic paradigm. It involved 05 Muslim educators in Tanzania. Face to face interviews were used and later transcribed verbatim. The results reveal understanding of life mission and purpose, holistic integrated knowledge, teaching for transformation, teaching activities as amānah (trust) and sense of being role model as major focuses of Muslim educators. Therefore, educating teacher ethics is the function of theoretical and practical knowledge, rational and spiritual sources of knowledge across disciplines.